The Influence of Logistic Performance Index Variable On The Competitive Advantage of Basic Non-Iron Metal Companies In Eastern Indonesia - Rachmat Akbar; Atong Soekirman; Erna S. Widodo (Dinasti Publisher, 2024)
Getting the right items to the right place at the right time under the appropriate conditions is the goal of logistics, which will benefit the business. Businesses took a while to understand how crucial logistics were to gaining a competitive edge over rivals. The research was conducted in nickel processing companies in the eastern part of Indonesia, specifically in Sulawesi, involving 2 (two) companies in the Konawe region, Southeast Sulawesi, and 1 (one) company in the North Morowali region, Central Sulawesi which have obtained bonded zone facilities from Customs. The research involves 100 respondents, consisting of employees and managers responsible for the supply chain and directly involved in logistic activities. The type of research is quantitative with a survey approach. Data is collected through instruments in the form of statement sheets with a Likert scale model that has been tested. Data analysis was carried out using multiple regression using SmartPLS. The results of the analysis show: (1) Customs and Excise have a significant positive effect on competitive advantage; (2) Infrastructure has a significant positive effect on competitive advantage; (3) International shipping has a significant positive effect on competitive advantage; (4) Service Quality has a significant positive effect on competitive advantage; (5) Search Tracking has a significant positive effect on competitive advantage; (6) Timeliness has a significant positive effect on competitive advantage. Several recommendations and policy implications were also presented.